A UHV MOKE magnetometer complementing XMCD‐PEEM at the Elettra Synchrotron. (30th March 2021) - Genuzio, Francesca; Giela, Tomasz; Lucian, Matteo; Menteş, Tevfik Onur; Brondin, Carlo Alberto; Cautero, Giuseppe; Mazalski, Piotr; Bonetti, Stefano; Korecki, Jozef; Locatelli, Andrea
Abstract : A UHV‐compatible MOKE magnetometer for in situ studies operating in tandem with the PEEM at the Nanospectroscopy beamline of the Elettra synchrotron. Abstract : We report on a custom‐built UHV‐compatible Magneto‐Optical Kerr Effect (MOKE) magnetometer for applications in surface and materials sciences, operating in tandem with the PhotoEmission Electron Microscope (PEEM) endstation at the Nanospectroscopy beamline of the Elettra synchrotron. The magnetometer features a liquid‐nitrogen‐cooled electromagnet that is fully compatible with UHV operation and produces magnetic fields up to about 140 mT at the sample. Longitudinal and polar MOKE measurement geometries are realized. The magneto‐optical detection is based on polarization analysis using a photoelastic modulator. The sample manipulation system is fully compatible with that of the PEEM, making it possible to exchange samples with the beamline endstation, where complementary X‐ray imaging and spectroscopy techniques are available. The magnetometer performance is illustrated by experiments on cobalt ultra‐thin films, demonstrating close to monolayer sensitivity. The advantages of combining in situ growth, X‐ray Magnetic Circular Dichroism imaging (XMCD‐PEEM) and MOKE magnetometry into a versatile multitechnique facility are highlighted.